PEOPLE'S BUSINESS CREDIT: OMNIBUS LAW AND BUSINESS REENGINEERING COMMUNITY FINANCIAL INSTITUTIONS - Murwadji, Tarsisius; Tresna Puja Asmara, Teguh; Kusuma, Sylvia (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2020)
ABSTRACTThe Government's program to accelerate the development of the real sector and the empowerment of Micro, Small and Medium Enterprises (MSMEs), one of which is set forth in the policy package for the distribution of People's Business Credit (KUR). However, in its implementation, the KUR program experienced several problems and could not be carried out only by relying on funds from the Government or banks for the development of MSMEs. This is due to the fact that banks in conducting their business must always pay attention to the principle of banking prudence, while the KUR program requires banks to relax the conditions of their debtors who want to obtain credit or financing. This research uses the normative juridical approach method by emphasizing the study of literature and supported by data from field research. The results showed that the KUR program in its implementation could be synergized with the Corporate Social Responsibility (CSR) program. The CSR program can be a solution to the problems faced by the KUR program where later the CSR program can be used as a trigger for banking business reengineering in implementing the KUR program that can provide benefits for stakeholders. Keywords: People's Business Credit, Corporate Social Responsibility, Business Reengineering